Effect of skiing speed on ski forces in diagonal skiing - Vähäsöyrinki, P.; Komi, P.; Ishikawa, M.; Salmi, J.; Linnamo, V. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Force production plays an important role in diagonal skiing. A diagonal step can be divided into several phases (Komi and Norman 1987) and when the speed of a skier varies, produced forces may change according to speed. This study examined the effect of skiing speed on ski forces in diagonal skiing on a low uphill.